2004
DOI: 10.1259/bjr/58217479
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural haematoma during pregnancy: case report and review of the literature

Abstract: Spontaneous epidural haematoma is rare in pregnancy and only five cases have been reported. We present a case of a 31-year-old female G2P1 who at 32 weeks of gestation developed progressive ascending paralysis and numbness to a level of approximately T4. An urgent MRI of the spine was performed, which demonstrated a posterior epidural lesion at T1-T4 level. The lesion showed signal changes consistent with an epidural haematoma in the hyperacute stage. An emergency cesarean section was performed followed by spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…A further three articles were excluded; the first as it was the same case as reported in another study, published in another language, 9,10 the second because the article presented SEH occurring after chiropractic manipulation 11 and the third reported a case of unilateral epidural nerve root hematoma in a pregnant patient. 12 The remaining 21 articles were all case report design; 4,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to be noted, the article by Tada et al 30 reported 3 cases, making a total of 23 cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further three articles were excluded; the first as it was the same case as reported in another study, published in another language, 9,10 the second because the article presented SEH occurring after chiropractic manipulation 11 and the third reported a case of unilateral epidural nerve root hematoma in a pregnant patient. 12 The remaining 21 articles were all case report design; 4,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to be noted, the article by Tada et al 30 reported 3 cases, making a total of 23 cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…4,[14][15][16][17][18]20,21,[23][24][25][26][27][28][29][30] The hematoma was located in the anterior epidural space in 7 cases and the posterior epidural space in 14 cases. In two cases, the antero- Abbreviations: Ant, anterior; C, cervical; CS-D, cesarean section delivery; G1, first gestation; Gest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a rare occurrence during pregnancy, with only six cases reported in the literature [12]. Statistically, idiopathic cases account for approximate 40% of all cases [13] [14]. The most common site of a spontaneous spinal epidural hematoma is the cervicothoracic region or thoracolumbar region [7] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Valsalva maneuvers, such as straining, coughing, or lifting, increase intra abdominal and intrathoracic pressure [6] [22]. This, in turn, is transferred to the spinal epidural venous system and is thought to contribute to the rupture and hemorrhage of the epidural venous vessels [14] [23]. The typical clinical presentation of SSEH is the sudden onset of severe back, neck or inter scapular pain followed by progressive neurological deficits (paraparesis or quadriparesis).…”
Section: Discussionmentioning
confidence: 99%